PROPOLIS AMELIORATES TUMOR NEROSIS FACTOR-α, NITRIC OXIDE LEVLS, CASPASE-3 AND NITRIC OXIDE SYNTHASE ACTIVITIES IN KAINIC ACID MEDIATED EXCITOTOXICITY IN RAT BRAIN - Swamy, Mummedy; Hashim, Dian Suhaili; Sirajudeen, K. N .S.; Mustapha, Zulkarnain; Govindasamy, Chandran (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Increased nitric oxide (NO), neuronal inflammation and apoptosis have been proposed in excitotoxicity resulting in many neurodegenerative diseases. To understand the neuro-protective effects of propolis, activities of Nitric oxide synthase (NOS) and caspase-3 along with NO and tumor necrosis factor-α (TNF-α) levels were studied in cerebral cortex (CC), cerebellum (CB) and brain stem (BS) of rats supplemented with propolis and administered with kainic acid (KA).Materials and methods: Male Sprague-Dawley rats were divided into four groups; Control group and KA group received vehicle and saline. Propolis group and propolis + KA group were orally administered with propolis (150mg/kg body weight), five times every 12 hours. KA group and propolis +KA group were injected subcutaneously with kainic acid (15mg/kg body weight) and were sacrificed after 2 hrs, CC, CB and BS were separated, homogenized and used for estimation of NOS, caspase-3, NO and TNF-α by commercial kits. Results were analyzed by one way ANOVA, reported as mean + SD (n=6), and p<0.05 considered statistically significant.Results: The concentration of NO, TNF-α, NOS and caspase-3 activity were increased significantly (p<0.001) in all the three brain regions tested in KA group compared to control. Propolis supplementation significantly (p<0.001) prevented the increase in NOS, NO, TNF-α and caspase-3 due to KA.Conclusion: Results of this study clearly demonstrated that the propolis supplementation attenuated the NOS, caspase-3 activities, NO, and TNF-α concentration and in KA mediated excitotoxicity. Hence propolis can be a possible potential protective agent against excitotoxicity and neurodegenerative disorders.